2001
DOI: 10.1159/000055734
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Three-Dimensional Magnetic Resonance Imaging of the Vestibular Labyrinth in Patients with Atypical and Intractable Benign Positional Vertigo

Abstract: Benign paroxysmal positional vertigo (BPPV) is a most common cause of dizziness and usually a self-limited disease, although a small percentage of patients suffer from a permanent form and do not respond to any treatment. This persistent form of BPPV is thought to have a different underlying pathophysiology than the generally accepted canalolithiasis theory. We investigated 5 patients who did not respond to physical treatment, presented with an atypical concomitant nystagmus or both with high-resolution three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…However, when 5 or 6 maneuvers are ineffective and once typical features of the nystagmus are observed, these patients should be assessed by a specific neuro-radiological study to rule out CNS conditions [9] . After CNS involvement has been ruled out, the persistence of positional vertigo symptoms should lead us to consider morpho-structural alterations of the labyrinth as well as metabolic and functional labyrinth conditions that facilitate the formation and maintenance of canaliths [8,12,13] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, when 5 or 6 maneuvers are ineffective and once typical features of the nystagmus are observed, these patients should be assessed by a specific neuro-radiological study to rule out CNS conditions [9] . After CNS involvement has been ruled out, the persistence of positional vertigo symptoms should lead us to consider morpho-structural alterations of the labyrinth as well as metabolic and functional labyrinth conditions that facilitate the formation and maintenance of canaliths [8,12,13] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies based on this technique have shown that patients with persistent BPPV had a higher incidence of abnormal MRI images (stenosis and canal filling defects) than normal controls [11][12][13] . These anomalies might correspond to really ductal narrowness or to plugs of otoconial debris [11,12] . Preliminary reports about these labyrinth abnormalities led us to consider the use of steroids because of their anti-inflammatory effect since glucocorticoid receptors are prevalent throughout the inner ear, including the vestibular structures (such as maculae of the utricle and saccule, otoconial membrane, the semicircular canal cristae, semicircular canal duct epithelium, and extramacular epithelium of the saccule) [15,18] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations